Capital Structure and Performance due to Gender Diversity of CEOs in Indonesian Small & Medium-sized Business - Titik Kristanti, Farida; Rahayu, Sri (International Journal of Engineering and Technology, 2018)
Previous researches and results show that women-owned small firms have less debt than man-owned firms, and they have different performance. The objective of this study is to know whether the difference of capital structure is a factor correlated with gender differences resulting in different financial performance. This study utilizes sample data of all small and medium-sized businesses listed in Indonesia Stock Exchange to determine the differences of capital structure and performance between companies with male and female CEOs. The statistical test result using independent t-test shows that there is no difference in both of them. Regression result shows variables influencing capital structure of small and medium-sized businesses in Indonesia are age of company, company size and company liquidity. Meanwhile, for company performance, the statistical test result shows that it is only variables of age of company and leverage that have significant effect. Therefore, small and medium-sized businesses should maintain their capital structure at low rates to have a good financial performance. Companies that are able to survive in a long term will also increase the company performance.Â Â Â